FPGA implementation of MCPFSK modulation for HF data communication - Fitri Dewi, Jaswar; Ahmad Zuri, Sha’ameri (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.